DISCIPLINES AND THE CATEGORIZATION OF SCIENTIFIC TRUTH: THE CASE OF SOCIAL SCIENCES IN THE HEBREW WIKIPEDIA - Bar-haim, Eyal (Journal of Sociocybernetics, 2018)
For the general audience, Wikipedia is considered the source of “truth,” especially for scientific knowledge. While studies of Wikipedia usually focus around the accuracy of the knowledge within it, few studies have explored its hierarchy and categorization. This study aims to describe how scientific information is organized into disciplines in Wikipedia. I take as a case study the Hebrew Wikipedia () and examine the representation and interrelations of five social sciences: sociology, anthropology, economics, political science, and psychology. I gather data from Wikipedia entries categorized under each of these disciplines and create a network that contains categories and subcategories derived from these entries. Using network analysis techniques, I estimate the strength of the relations between the disciplines. I find that while sociology, anthropology, and political science are strongly linked to each other, psychology and economics are relatively isolated. An interesting case is the distance between economics and sociology, since under the subcategory “Inequality,” the entries are uniquely categorized under sociology or economics but rarely under both categories. I claim this is an example of a fractal walk in the distinction between the two disciplines. As there is a hierarchical difference between these disciplines, the end result is a hierarchical value of the scientific knowledge presented in these Wikipedia entries.